AutoCAD 2017 3D modeling - Hamad, Munir M. (Mercury Learning and Information, 2017)
This book provides new and seasoned users with step-by-step procedures on creating and modifying 3D models, working with cameras and lights, assigning materials to objects, rendering, and printing. Unlike many AutoCAD competitors, it uses both metric and imperial units to illustrate the myriad tools for this popular application.